Metadiscourse in Lithuanian linguistics research articles: A study of interactive and interactional features - Ruskan, Anna; Maslauskienė, Greta (Kalbotyra, 2024)
In the recent decades the interpersonal nature of written academic communication has been widely studied in various linguistic/cultural contexts, including Lithuanian. To gain new insights into how knowledge is negotiated interpersonally in Lithuanian scientific texts, the present paper explores the distribution and use of interactive and interactional features of metadiscourse in Lithuanian research articles in a single discipline, i.e., linguistics. For the classification of metadiscourse resources, the study employs the interpersonal model of metadiscourse (Hyland 2005a). Based on the analysis of 30 Lithuanian research articles in the field of linguistics, this exploratory investigation reveals rhetorical strategies utilized by professional authors to construct a coherent text and engage their audiences in the chosen disciplinary domain. The dominance of interactive metadiscourse features over interactional ones in the corpus examined shows that Lithuanian authors of research articles in linguistics are generally more concerned with organizing discourse and guiding readers through the text than with expressing attitudes and commitment to their arguments. The most common interactive resources are transitions and evidentials, and the most frequent interactional devices include boosters, engagement markers, and hedges. The analysis offers a number of methodological steps necessary for applying the interpersonal model of metadiscourse to Lithuanian data, and complements numerous investigations into Lithuanian academic discourse by illustrating and discussing the writer-reader interaction in linguistics in a larger corpus.